PCV-15 and PPSV-23 coverage of invasive and respiratory tract Streptococcus pneumoniae, including MDR and XDR isolates: CANWARD 2007–20. (10th February 2022) - Golden, Alyssa R.; Baxter, Melanie; Adam, Heather J; Martin, Irene; Demczuk, Walter; Mulvey, Michael R; Karlowsky, James A; Zhanel, George G
Abstract: Objectives: To compare the proportion of invasive and respiratory tract isolates of Streptococcus pneumoniae, including MDR and XDR strains, that demonstrated PCV-15 and PPSV-23 serotypes in Canada from 2007 to 2020. Methods: The CANWARD study collected 2984 S. pneumoniae isolates from 2007 to 2020 (1054 invasive, 1930 respiratory). Serotyping was performed using the Quellung reaction. Antimicrobial susceptibility testing was performed using CLSI methods. MDR/XDR was defined as resistance to ≥3/≥5 antimicrobial classes, respectively. Results: Overall, the proportion of vaccine serotypes demonstrating a PCV-15/PPSV-23 serotype was significantly higher in blood isolates (54.6%/76.2%, respectively) than respiratory isolates (38.9%/55.3%; P < 0.0001). Similarly, PCV-15 and PPSV-23 vaccine coverage was higher for blood isolates for all demographic categories, including both genders, all regions and all age groups ( P ≤ 0.0213). PCV-15/PPSV-23 coverage was also significantly higher for blood isolates demonstrating clarithromycin resistance (60.4/75.1% blood, 47.8/57.4% respiratory; P ≤ 0.009) and penicillin resistance (68.9/63.0% blood, 45.2/43.0% respiratory; P < 0.0001) and trimethoprim/sulfamethoxazole-resistant isolates for PPSV-23 only (82.6% blood, 64.3% respiratory; P = 0.0057). Vaccine coverage was numerically higher but not significantly different between specimen source for children <2 years of age, as well as ceftriaxone-, doxycycline- and levofloxacin-resistant isolates. PCV-15/PPSV-23 vaccine coverage for MDR isolates (61.8%/67.3% blood, 52.2%/56.2% respiratory) and XDR isolates (93.3% blood, 89.6% respiratory for both vaccines) was not significantly different between specimen sources. Conclusions: PCV-15 and PPSV-23 serotype coverage is generally greater for blood versus respiratory isolates but not for MDR and XDR isolates. Continued pneumococcal surveillance is warranted to determine future trends in vaccine coverage, serotype distribution and antimicrobial susceptibilities under the pressure of vaccine use.